The battle over “food addiction” - Lustig, Robert H. (Frontiers in Psychiatry, 2025)
Despite decades of nutrition, obesity, and diabetes research, and worsening prevalences and severities of virtually every chronic metabolic disease, the scientific community remains divided over the existence and veracity of the concept of food addiction. There are numerous rationalizations — 1) you need food to survive, (of which “Food is Medicine” is the latest mantra); 2) people with obesity should not be stigmatized as “mentally ill”; 3) people with obesity should instead adhere to “personal responsibility”; 4) the data are incomplete and not strong enough; 5) it’s correlation but not causation; 6) everyone is exposed, but not everyone is addicted; 7) there is no “withdrawal” phenotype; and 8) it’s not “food addiction” but “eating addiction”. All are in play, yet more health care dollars are diverted to the treatment of food-related disease every year. While various ingestible chemicals (e.g. nicotine, cocaine, heroin, alcohol) are clearly addictive, it appears to be a stretch by some scientists to argue that individual substances found in food (e.g. sugar, caffeine), or the food itself (e.g. ultraprocessed food), rise to meet the same criteria. Symposia on food addiction proliferate and journal debates continue. The definition of addiction consists of numerous criteria, including public health demographics, biochemistry, imaging, animal trials, clinical trials, and economics. None of these have proven to be “slam dunks” to align a general consensus. But paramount for scientific acceptance is the delineation of mechanism. This article will review the history of the controversy, the data on which foods are most likely to be addictive, the two mechanisms involved in the pathogenesis of food addiction and relate it to the most likely culprits, and the role of the food industry in promulgating false narratives, in order to provide a rational way forward from this debate.